Guidelines for Administration of Graduate Programs Based on the Principles of Aparihaniyadhamma In Mahachulalongkornrajavidyalaya University, Surin Campus - Srithong, Thanoo; Tongtip, Taweesak; Chinnawong, Wiset; Pakprom , Sathaporn; Pradubsook, Chuchai (Academic MCU Buriram Journal, 2025)
This research aimed to study the current conditions, the usage of Aparihaniyadhamma principles, and to propose guidelines for graduate programs administration based on the principles of Aparihaniyadhamma in Mahachulalongkornrajavidyalaya University, Surin Campus. The research design used was the mixed-methods research i.e. quantitative and qualitative studies. The research instruments were questionnaires and focus group discussions. Quantitative data were collected from 46 target groups on the current situation and 23 target groups on the principle of non-transgression. Qualitative data were 10 key informants for focus group discussion. Data analysis was done by quantitative and descriptive methods. The research results were found as follows: 1. Current conditions of graduate programs administration in Mahachulalongkornrajavidyalaya University, Surin Campus, were overall rated as a high level. When considering each aspect, it was found that all aspects were at a high level. The aspect with the highest average value was the aspect of standard supervision, followed by the aspect of student research promotion, and the aspect with the lowest average value was the aspect of procurement and development of learning support. 2. Principles of Aparihaniyadhamma in the graduate programs administration at Mahachulalongkornrajavidyalaya University, Surin Campus, were overall rated as a highest level. When considering each aspect, it was found that there were 5 aspects at the highest level, 4 aspects at the high level, and the aspect with the highest average value was graduate quality work, followed by standard supervision work, and the aspect with the lowest average value was learning support procurement and development work. 3. Guidelines for graduate program administration based on the principles of Aparihaniyadhamma in Mahachulalongkornrajavidyalaya University, Surin Campus, were found that there were 9 aspects, 18 issues, and 40 guidelines, namely, 8 guidelines for standards supervision, 4 guidelines for graduate quality, 6 guidelines for student promotion and development, 4 guidelines for faculty management and development, 2 guidelines for curriculum, teaching and learning, and student assessment, 4 guidelines for learning support and development, 2 guidelines for student research promotion, 4 guidelines for extra-curricular activities, and 4 guidelines for general administration. The principles of Aparihaniyadhamma could be applied to graduate program administration.